Exploration of OSCE Results to Evaluate Medical Students’ Progress on Learning Eye Examination in Clinical Skills Laboratory - Widyandana Widyandana; Angela Nurini Agni; Agus Supartoto; Suhardjo Suhardjo (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Medical student learn how to perform eye examinations since beginning in clinical skills laboratory. Objective Structured Clinical Examination (OSCE) was used to assess students’ clinical skills performance every year and to indicate students’ progress. To evaluate medical students’ clinical skills progress, and to evaluate OSCE of eye examination skills. Methods: A cohort study, involving first and third year OSCE results in Clinical Skills Laboratory, Faculty of Medicine Gadjah Mada University from medical students batch 2010 (n:185). The scores of OSCE Year 1 compared to Year 3 using Mann whitney test to explore the progress of students clinical skills performance. To correlate between OSCE scores with clinical cases used in OSCE (such as: visual aquity, visual field, segment anterior and posterior examination) using Pearsoncorrelation to evaluate the assessment process. Result: OSCE results show that medical studens give significant progress on their eye examination performance (median OSCE year 1=66, year 3=80; p=0.00). There is strong correlation between clinical cases during OSCE with students score (p=0.005) that show inequality of difficulty level of cases, particularly for first year OSCE that used more detail check list instrument. Conclusion: Medical students show significant progress on their eye examination skills performance. OSCE process need to be improved, especially on developing clinical cases and check list as a scoring instrument. Keywords: medical students, eye examination, OSCE score